Synthesis of Thymidine, Uridine, and 5‐Methyluridine Nucleolipids: Tools for a Tuned Lipophilization of Oligonucleotides. Issue 5 (17th May 2013) - Werz, Emma; Viere, Rebecca; Gassmann, Gina; Korneev, Sergei; Malecki, Edith; Rosemeyer, Helmut
Abstract Three pyrimidine nucleosides, uridine (1), 5‐methyluridine (6), and 2′‐deoxythymidine (11), were converted to amphiphilic nucleolipids. Compounds 1 and 6 were lipophilized by introduction of symmetric ketal moieties with various carbon chain lengths (i.e., 5–17). Two ketal derivatives, 2b and 7a, were additionally further hydrophobized by N(3)‐farnesylation. 2′‐Deoxythymidine was alkylated at N(3) with a cetyl (=hexadecyl) residue, either directly or, after complete orthogonal protection of the sugar OH groups, by Mitsunobu reaction with hexadecan‐1‐ol. Some of the nucleolipids were subsequently converted to their 2‐cyanoethyl phosphoramidites (5′ or 3′), one of which was used for an exemplary synthesis of a lipo‐oligonucleotide. The sequence of this lipo‐oligonucleotide is an encoded manifestation of Pythagoras' law, created with a key table in which the letters of the alphabet, the numbers from 0 to 9 as well as the mostly used mathematical symbols are allocated to a ribonucleic acid triplet of the genetic code.